Quality assurance in radiation oncology. (5th April 2021) - FitzGerald, Thomas J.; Followill, David; Laurie, Fran; Boterberg, Tom; Hanusik, Richard; Kessel, Sandra; Karolczuk, Kathryn; Iandoli, Matthew; Ulin, Kenneth; Morano, Karen; Bishop‐Jodoin, Maryann; Kry, Stephen; et al.
Abstract: The Children's Oncology Group (COG) has a strong quality assurance (QA) program managed by the Imaging and Radiation Oncology Core (IROC). This program consists of credentialing centers and providing real‐time management of each case for protocol compliant target definition and radiation delivery. In the International Society of Pediatric Oncology (SIOP), the lack of an available, reliable online data platform has been a challenge and the European Society for Paediatric Oncology (SIOPE) quality and excellence in radiotherapy and imaging for children and adolescents with cancer across Europe in clinical trials (QUARTET) program currently provides QA review for prospective clinical trials. The COG and SIOP are fully committed to a QA program that ensures uniform execution of protocol treatments and provides validity of the clinical data used for analysis.